Model Agroforestry Berbasis Jelutung Rawa (Dyera polyphylla Miq) di Kabupaten Katingan dan Kota Palangka Raya: Agroforestry Model Based on Swamp Jelutung (Dyera polyphylla Miq) in Katingan Regency and Palangka Raya City - Johanna Maria Rotinsulu; Raden Mas Sukarna; Nuwa Nuwa; Nursiah Nursiah; Sampang Sampang (JURNAL HUTAN TROPIKA, 2026)
The implementation of social forestry is becoming increasingly important, especially in degraded and deforested peat swamp forest ecosystems. One of the fundamental aspects of agroforestry is maintaining soil fertility. The feasibility of developing agroforestry to rehabilitate degraded forests and peatlands is based on jelutung swamp research to achieve optimal and sustainable results. Forestry sector policies and implementation will continue to be strengthened and improved in line with the impacts of climate change, such as agroforestry-based jelutung RHLG activities. The research objectives are to analyze the growth of community jelutung swamp plants based on age class and assess the economic feasibility of jelutung plants based on agroforestry patterns. The method used in this study is purposive sampling, by selecting and determining jelutung plants based on age class, with a sampling intensity of ±5% of the area or the number of plants. The results of measuring diameter, tree height, and regression correlation tests are presented in tables and graphs. Furthermore, an analysis is conducted to examine the role of social forestry with jelutung plants using Net Present Value (NPV), Benefit-Cost Ratio (BCR), and Internal Rate of Return (IRR). The results show that the growth of jelutung plants in Hampangen Village and Kalampangan Subdistrict varies, with average diameter values of 24.03 cm and 18.71 cm, and average tree heights of 14.57 m and 11.54 m. Based on the three criteria used (NPV, BCR, IRR), the intercropping agroforestry system with jelutung as the main crop can be developed and is economically viable because it is profitable.